The Emotional Dimensions of Animal Disease Management: A Political Ecology Perspective for a Time of Heightened Biosecurity - Epstein, Kathleen; von Essen, Erica; Wilmer, Hailey (Frontiers in Human Dynamics, 2021)
The ongoing devastation of the Covid-19 pandemic has brought new urgency to questions surrounding the origins, management, and complex dynamics of infectious diseases. In this mini review, we use growing international concern over the pandemic potential of emerging infectious diseases as motivation for outlining a research approach to study the emotional dimensions of animal disease management. We sketch out this important analytical terrain by first locating opportunities for literature on the biosecurization of nature to intersect with the emerging field of emotional political ecology. Second, we describe three biosecurity contexts and environmental conflicts at the wildlife-livestock interface: African swine fever in wild boar, brucellosis in elk, and pneumonia in bighorn and domestic sheep. We argue that in these “contact zones,” a focus on emotions can add a new layer of explanation for analyzing the manifestations, implications, and varied experiences of biosecurity.